Pengaruh Jam Layanan Perpustakaan Fakultas Adab dan Bahasa Terhadap Minat kunjung Mahasiswa Ilmu Perpustakaan dan informasi islam (2022-2023): Pengaruh Jam Layanan Perpustakaan Fakultas Adab dan Bahasa Terhadap Minat kunjung Mahasiswa Ilmu Perpustakaan dan informasi islam (2022-2023) - Ananda farel (Universitas Islam Negeri Salatiga, 2026)
The Library of the Faculty of Adab and Humanities (FAB) plays a strategic role as an information center and learning space for students, particularly those in the Islamic Library and Information Science Study Program (IPII). This study aims to analyze the influence of library service hours on the visitation interest of IPII students from the 2022–2023 cohort. The research employs a descriptive quantitative method, collecting data through Likert-scale questionnaires and semi-structured interviews with librarians. The results indicate that the majority of students consider the current library service hours adequate and convenient for their visits; however, challenges arise regarding the consistency of service hours due to the limited number of librarian staff. Uncertainty in service hours affects three dimensions of the SERVQUAL theory: Reliability, Responsiveness, and Assurance, which directly impact students’ visitation interest. Students tend to visit the library more frequently when service hours are flexible, consistent, and reliable. This study emphasizes the importance of effectively managing library service hours, either by increasing staff or establishing backup schedules, to enhance visitor interest and user satisfaction. The findings are expected to serve as a basis for evaluating and improving FAB library services in the future.